Retrograde peri-implantitis: report of a case successfully treated by resection of the implant apex (2021)
Retrograde peri-implantitis (RPI) is a periapical lesion that develops after implant insertion in which the coronal portion of the implant achieves a normal bone-to-implant interface. The most common etiology of RPI is the presence of an adjacent endodontic lesion. In most of the case reports available in the literature, the diagnosis of RPI occurred between 1 week and 4 years after implant placement. This case report illustrates the treatment of RPI that occurred more than 15 years after implant loading, caused by endodontic infection of the adjacent tooth.